Variations in leptin, nesfatin-1 and irisin levels induced by aerobic exercise in young trained and untrained male subjects - Algul, Sermin; Ozdenk, Cagri; Ozcelik, Oguz (Inst Sport, 2017)
The aims of this study were to investigate the impacts of acute aerobic exercise on circulating levels of hormones associated with energy metabolism, namely leptin, nesfatin-1 and irisin, in trained and untrained male subjects and to determine whether the timing of the exercise (i.e. morning or night) amplified these impacts. Thirty trained (19.2 +/- 0.7 years) and 30 untrained (19.5 +/- 0.6 years) male subjects performed two aerobic running exercises (3 days between tests) to 64-76% of the subjects' maximal heart rate for about 30 min. Pre- and post-exercise venous blood samples were taken and analysed for leptin, nesfatin-1 and irisin using enzyme-linked immunosorbent assay (ELISA). Paired samples and independent samples t-tests were used to analyse data. Irisin levels increased in all the subjects (p<0.001). In both groups, nesfatin-1 levels increased significantly after the night-time exercise (p<0.05). Importantly, leptin and nesfatin-1 levels varied among the trained and untrained groups: Both leptin and nesfatin-1 levels increased in 4 (13%) and 12 (40%) subjects, respectively, after the morning exercises, and they increased in 9 (30%) and 10 (33%) subjects, respectively, after the night-time exercise. They decreased in 5 (16%) and 7 (23%) subjects, respectively, after the morning exercise and in 6 (20%) and 3 (10%) subjects, respectively, after the night-time exercise. Exercise may result in increased energy consumption by altering irisin levels. However, due to variations among individuals, increasing leptin and nesfatin-1 levels by reducing food intake may not be applicable.
Keywords: Irisin; Leptin; Nesfatin-1; Aerobic exercise; Individual variation